Epigenetic modulations in early endothelial cells and DNA hypermethylation in human skin after sulfur mustard exposure. (26th February 2016) - Steinritz, Dirk; Schmidt, Annette; Balszuweit, Frank; Thiermann, Horst; Simons, Thilo; Striepling, Enno; Bölck, Birgit; Bloch, Wilhelm
Highlights: Sulfur mustard induced epigenetic modulations were explored in early endothelial cells. 78 Genes related to epigenetic pathways and global DNA methylation were investigated. SM exposure resulted in complex epigenetic perturbations and DNA methylation in vitro . Increased DNA methylation was found in SM exposed human skin one year after exposure. Epigenetic modulations may be responsible for SM-induced long-term health effects. Abstract: Victims that were exposed to the chemical warfare agent sulfur mustard (SM) suffer from chronic dermal and ocular lesions, severe pulmonary problems and cancer development. It has been proposed that epigenetic perturbations might be involved in that process but this has not been investigated so far. In this study, we investigated epigenetic modulations in vitro using early endothelial cells (EEC) that were exposed to different SM concentrations (0.5, 1.0, 23.5 and 50 μM). A comprehensive analysis of 78 genes related to epigenetic pathways ( i.e., DNA-methylation and post-translational histone modifications) was performed. Moreover, we analyzed global DNA methylation in vitro in EEC after SM exposure as a maker for epigenetic modulations and in vivo using human skin samples that were obtained from a patient 1 year after an accidently exposure to pure SM. SM exposure resulted in a complex regulation pattern of epigenetic modulators which was accompanied by a global increase of DNA methylation in vitro . Examination of the SM exposed human skin samples also revealed a significant increase of global DNA methylation in vivo, underlining the biological relevance of our findings. Thus, we demonstrated for the first time that SM affects epigenetic pathways and causes epigenetic modulations both in vivo and in vitro.